Pre-breeding studies in Panicum coloratum var. coloratum: Characterization using agro-morphological traits and molecular markers = Estudios de pre-mejoramiento genético en Panicum coloratum var. coloratum : caracterización usando marcadores moleculares y caracteres agro-morfológicos - Burgos, Estanislao; Thompson, Carolina Soledad; Giordano, Mabel Cristina; Tomas, Maria Andrea (CIAT, 2018)
Panicum coloratum var. coloratum is a native African perennial C4 grass, introduced to Argentina. It is tolerant of salinity and cold and has good forage production. The scarce genotypic and phenotypic information about this grass limits its breeding in order to satisfy market demands. The aim of this study was to evaluate the variability in a collection of Panicum coloratum var. coloratum formed by 8 accessions and grown at EEA INTA Rafaela during the summer of 2011, based on 15 ISSR molecular markers and 17 morphological characters. For all morphological characters, the distribution of variability observed in the collection was high and not homogenous. The characters that showed greater variation were related to forage and seed production. Eight ISSRs, selected according to their reproducibility, showed 127 bands with 100% polymorphism and allowed grouping of populations according to their site of collection. AMOVA study indicated that more than 58% of the molecular variation existed within accessions; this would be consistent with the predominant allogamous form of reproduction. The results showed that the combined use of molecular and morphological markers offer complementary information. The high variability detected in this collection will allow for the initiation of a breeding program to improve important characters like those related to DM yield and seed production.